2023
DOI: 10.1186/s13018-023-03665-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spinal deformities on lung development in children: a review

Abstract: Scoliosis before the age of 5 years is referred to as early-onset scoliosis (EOS). While causes may vary, EOS can potentially affect respiratory function and lung development as children grow. Moreover, scoliosis can lead to thoracic insufficiency syndrome when aggravated or left untreated. Therefore, spinal thoracic deformities often require intervention in early childhood, and solving these problems requires new methods that include the means for both deformity correction and growth maintenance. Therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 126 publications
(151 reference statements)
0
7
0
Order By: Relevance
“…Pediatric spine deformity surgeons have a variety of operative techniques to control early onset scoliosis to prevent the development of thoracic insufficiency syndrome. Both Redding and Wang recently concluded that it is important to monitor the impact of different surgical strategies on pulmonary development including the use of various surgical devices and anchor points [32, 33]. However, little data exists, and hence information regarding the long-term changes in lung function during spinal surgical and non-surgical treatments for EOS must be expanded upon [33].…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric spine deformity surgeons have a variety of operative techniques to control early onset scoliosis to prevent the development of thoracic insufficiency syndrome. Both Redding and Wang recently concluded that it is important to monitor the impact of different surgical strategies on pulmonary development including the use of various surgical devices and anchor points [32, 33]. However, little data exists, and hence information regarding the long-term changes in lung function during spinal surgical and non-surgical treatments for EOS must be expanded upon [33].…”
Section: Discussionmentioning
confidence: 99%
“…Scoliosis is a complex spinal deformity characterized by curvature of the vertebral column [1][2][3]. Due to deformity of the spine, scoliosis can significantly affect respiratory function by inducing asymmetric deformation of the chest wall and affecting the function of respiratory muscles [4][5][6]. Understanding how scoliosis influences respiratory function has been a subject of increasing interest in both medical and scientific communities, as it can aid in early detection, diagnosis, and appropriate management of the condition [7].…”
Section: Introductionmentioning
confidence: 99%
“…EOS frequently co-occurs with TIS, establishing a potent interconnection that perpetuates a detrimental cycle. On the one hand, scoliosis causes thoracic deformity, thereby affecting the development and function of the lungs, and is one of the triggers of TIS [ 4 , 5 ]. On the other hand, TIS leads to an imbalance in the muscle groups, which has an impact on the normal growth and development of the spine, leading to EOS [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, scoliosis causes thoracic deformity, thereby affecting the development and function of the lungs, and is one of the triggers of TIS [ 4 , 5 ]. On the other hand, TIS leads to an imbalance in the muscle groups, which has an impact on the normal growth and development of the spine, leading to EOS [ 4 , 5 ]. Notably, pulmonary hypoplasia, a primary characteristic of patients with the EOS + TIS, induces respiratory failure, which is the main cause of dying prematurely in patients [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation